OPTIMIZATION OF THE REPLACEMENT PROCESS FOR THE BRAKE SHOES ISUZU GIGA TRUCK AT PT AI-ISO DM JAKARTA BRANCH - Manurung, Vuko A T; Dwicahyo, Mohammad R.; Wibowo, Yohanes T.; Haryadi, Setyo (AUSTENIT, 2023)
PT AI-ISO workshop on DM Jakarta provides various repair and periodic maintenance services. In periodic maintenance, brake repair jobs have problems replacing the brake pads (brake shoe set) of Isuzu Giga Trucks, which takes about 9 hours. To reduce the processing time, an improvement process is carried out to shorter processing time, so the customer feels more satisfied with repairing his vehicle. From observations, the length of work time was due to the process of changing the brake pads outside the workshop due to the absence of tools to install the brake pads. The repair shop offers to replace a set of brake pads, but the price is higher than just replacing the brake pads, so the customer makes this choice. The improvement made was the manufacture of a rivet installation tool on the brake pads based on the workings of a rivet machine. First, it is necessary to make a brake pad holder so that it does not shift when pressed and ensures that the pressure acting on the rivet is as requested. This tool is also equipped with a Standard Operation Procedure to make it easier for technicians to replace brake pads. The result is a decrease in processing time for the brake pad replacement process from an average of 9 hours to 5 hours. With these tools, repairing the brake system can be accelerated and within the safe limits required in the vehicle's manual, and the customer will be more satisfied.